Pancasilais Sufi: Kiai Asrori as a Portrait of Nationalist and Moderate Figure in Disruption Era - Shobah, Muhammad Nurush; Setiyani, Wiwik; Yaqin, Ainul; Hakim, Lukman (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2024)
The relationship between Islam and the state is still debatable in Indonesia. Pancasila, as the foundation of the state, is also often contested, even though it was formulated by the Indonesian founding fathers through a very serious academic debate. This study will examine the role of K.H. Ahmad Asrori Al-Ishaqi (hereafter Kiai Asrori) Kedinding Surabaya as a Pancasilaist Sufi. This is qualitative-based research, where the data were collected from Kiai Asrori's works and his lectures uploaded on YouTube, observations, and direct and indirect interviews. The findings show that Kiai Asrori is a Sufi who is able to demonstrate that there are similarities between the teachings of Sufism and nationalism, especially with Pancasila. Both even have a symbiotic association. Kiai Asrori is an ulama and a Sufi who upholds the values of nationalism and democracy, which are reflected in the Majelis Lima Pilar (Five Pillars Assembly) he established. This assembly was built on two foundations, namely the practice and teachings of Sufism and nationalism and democratic values.Contribution: This study will provide new insights into Sufi practices and teachings that align with Pancasila values reflected in the figure of Kiai Asrori.